Genome-wide association analysis of cystatin c and creatinine kidney function in Chinese women - Yang Cai; Hongyao Lv; Meng Yuan; Jiao Wang; Wenhui Wu; Xiaoyu Fang; Changying Chen; Jialing Mu; Fangyuan Liu; Xincheng Gu; Hankun Xie; Yu Liu; et al. (BMC Medical Genomics)
Abstract Background With increasing incidence and treatment costs, chronic kidney disease (CKD) has become an important public health problem in China, especially in females. However, the genetic determinants are very limited. The estimated glomerular filtration rate (eGFR) based on creatinine is commonly used as a measure of renal function but can be easily affected by other factors. In contrast, eGFR based on both creatinine and cystatin C (eGFRcr-cys) improved the diagnostic accuracy of CKD. To our knowledge, no genome-wide association analysis of eGFRcr-cys has been conducted in the Chinese population. Methods By conducting a Genome-Wide association study(GWAS), a method used to identify associations between genetic regions (genomes) and traits/diseases, we examined the relationship between genetic factors and eGFRcr-cys in Chinese women, with 1983 participants and 3,838,121 variants included in the final analysis. Result One significant locus (20p11.21) was identified in the Chinese female population, which has been reported to be associated with eGFR based on cystatin C (eGFRcys) in the European population. More importantly, we found two new suggestive loci (1p31.1 and 11q24.2), which have not yet been reported. A total of three single nucleotide polymorphisms were identified as the most important variants in these regions, including rs2405367 (CST3), rs66588571(KRT8P21), and rs626995 (OR8B2). Conclusion We identified 3 loci 20p11.21, 1p31.1, and 11q24.2 to be significantly associated with eGFRcr-cys. These findings and subsequent functional analysis describe new biological clues related to renal function in Chinese women and provide new ideas for the diagnosis and treatment development of CKD.